2015
DOI: 10.1111/1742-6723.12460
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Potential of medical scribes to allay the burden of documentation and enhance efficiency in Australian emergency departments

Abstract: The increasing burden of documentation experienced by doctors threatens the efficiency in EDs and increases the likelihood of documentation errors. Medical scribes afford the opportunity to allay this burden by removing a large component of the doctors' documentation task. Scribes have been embedded successfully in US EDs, and the effects have been mostly advantageous. The present paper provides a brief overview of the function of scribes and their potential contribution to Australian EDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…To the best of our knowledge, this study obtained the largest collection of patient experience data pertaining to a medical scribe program . Similar to previous studies, this study revealed that patient experience was largely the same between patients who encountered a scribe and patients who did not .…”
Section: Discussionsupporting
confidence: 78%
“…To the best of our knowledge, this study obtained the largest collection of patient experience data pertaining to a medical scribe program . Similar to previous studies, this study revealed that patient experience was largely the same between patients who encountered a scribe and patients who did not .…”
Section: Discussionsupporting
confidence: 78%
“…Four reviews examined interventions relating to models of care using support staff such as scribes and physician assistant roles in ED [8,18,[74][75][76]. A description of the characteristics for scribes and physician assistants interventions is provided in Table 7.…”
Section: Scribes and Physician Assistantsmentioning
confidence: 99%
“…We read with interest the recent paper by Cabilan and Eley. 1 The authors broadly review the scribe literature and how it might relate to Australasia and are supportive of the concept. We agree that there is a fundamental and growing issue with the utilisation of emergency physicians for a large amount of data entry.…”
Section: Dear Editormentioning
confidence: 99%